Pengaruh Macam Kompos By Product Kebun Kelapa Sawit pada Beberapa Jenis Tanah yang Berbeda terhadap Pertumbuhan Bibit Kelapa Sawit di Pre Nursery - Nurizki, Ilhan; Rochmiyati, Sri Manu; Noviana, Githa (AGROISTA : Jurnal Agroteknologi, 2024)
The research was carried out with the aim of finding out the effect of types compost by product in several types of soil on growth of oil palm seedlings in pre nursery which was carried out in Wedomartani Village, Sleman, Yogyakarta in December 2023-March 2024. It was prepared using factorial experimental method in a Complately randomized desaign which consist of two factors, namely the type of compost, there are 4 types of treatment (with out compost, solid, Mucuna bracteate, and empty bunches), and the type of soil there are 3 types, namely (regusol, latosol, grumosol). In the treatment with out compost (control), standard doses of NPK fertilizer were given. The results of research based on parameter data were analysed using variance at a 5% level, if the effect was real, it was further tested with DMRT at a 5%. The results showed that there was a real interaction between soil type and compost type on canopy fresh weight and leaf area. Providing solid compost, Mucuna bracteate, empty bunches and NPK fertilizer as controls gave the same effect.